IMPLEMENTATION OF CHARACTER-BASED EDUCATION AND SCHOOL CULTURE AT SDIT PERMATA BUNDA 1 BANDAR LAMPUNG - Abdul Hakim; Dedi Saputra; Nasrudin Harahap; Nurul Hidayati Murtafiah (IAI An Nur Lampung, 2022)
The alternative of character building of students can be done through school culture in accordance with the Grand Design of character education because the character as a character is built based on applicable values. Therefore, character education through the school culture that students have based on values ​​essentially shapes the child into a better character and in a positive direction. For this reason, the writer analyses the Implementation of Character-Based Education and School Culture at SDIT Permata Bunda 1 Bandar Lampung. This research is a descriptive study using a qualitative approach. Descriptive research tries to explain the current solution based on the data, then presents the data and interprets it. Data collection techniques in this study were interviews, observation, and documentation. For the sample, the principals and teachers of SDIT Permata Bunda 1 Bandar Lampung. The Qur'anic generation are youths who hold fast to the Qur'an, make the Qur'an as a guide for their lives, read, memorise and understand its contents, and practice it in all aspects of life in the world. Children's character education is a process of forming a child's character or personality and is used as a provision from childhood to adulthood. Therefore, character education is an important thing that must be given to children because these fundamental values ​​are needed in the future. Achievement is a standardised test to measure a student's knowledge and proficiency in one or more knowledge in a subject.